Multi-domain integrated modeling and verification for the ball screw feed system in machine tools. (December 2020) - Mei, Zaiwu; Chen, Liping; Ding, Jianwan
An accurate dynamic model for the computer numerical control machine tool feed system is of great significance to improve the machining accuracy. However, the accurate dynamic model of the feed system is difficult to be established because its dynamic characteristics not only depend on the performance of subsystems, such as mechanical, electrical, and control, but also on the interaction between them. In order to solve this problem, a modular modeling method based on a non-causal connection is proposed in this article, and the multi-domain seamless integrated model for the ball screw feed system is established. First, the feed system is decomposed by modularization, and the interface models in each domain are defined. Then all the subsystems are modeled strictly, and the nonlinear characteristics of each subsystem are analyzed. Finally, the multi-domain seamless integrated model of the ball screw feed system is established by the non-causal connection of subsystem models, and the experiment is carried out to validate the system model. The experimental results show that the multi-domain seamless integrated model of the ball screw feed system established in this article can accurately reflect the dynamic characteristics of the real physical system, and has high prediction accuracy for the dynamic following error. It is of great significance to further study the multi-domain coupling characteristics and compensation control methods of the machine tool system.